2018
DOI: 10.1007/s13748-018-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Review-aggregated aspect-based sentiment analysis with ontology features

Abstract: With all the information that is available on the World Wide Web, there is great demand for data mining techniques and sentiment analysis is a particularly popular domain, both in business and research. Sentiment analysis aims to determine the sentiment value, often on a positive-negative scale, for a given product or service based on a set of textual reviews. As fine-grained information is more useful than just a single overall score, modern aspect-based sentiment analysis techniques break down the sentiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Sophie de Lok et al, using ontology features proposed an aspect-based sentiment analysis on restaurant reviews data evolved from SemEval 2016 [13]. They defined 3 main ontology classes like Entity extraction, Generic positive/negative, sentiment.…”
Section: Related Workmentioning
confidence: 99%
“…Sophie de Lok et al, using ontology features proposed an aspect-based sentiment analysis on restaurant reviews data evolved from SemEval 2016 [13]. They defined 3 main ontology classes like Entity extraction, Generic positive/negative, sentiment.…”
Section: Related Workmentioning
confidence: 99%
“…They used the ontology to identify appropriate features after clustering and showed that the accuracy of the feature extraction greatly improved. Sophie et al (2018) focused on semantic enrichment by employing ontology features in determining the sentiment value of a given pair of review and feature. Chen et al (2018) designed a text analytics framework to assess secondhand sellers' reputations and developed a feature extraction method that combined the results of domain ontology and topic modeling to extract topical features.…”
Section: Product Review Domain Ontologymentioning
confidence: 99%
“…An an aspect level classification consists of the representation of sentiments as triplets {user, feature, sentiment}. In this sense, ontologies have been proved to be an effective method to extract the aspects for an specific domain [11][12][13][14][15][16].…”
Section: Opinion Miningmentioning
confidence: 99%